mHealth-based exercise vs. traditional exercise on pain, functional disability, and quality of life in patients with knee osteoarthritis: a systematic review and meta-analysis of randomized controlled trials - Tang, Liang; Wang, Meng-Ming; Wang, He-Xia; He, Xiao-Ya; Jiang, Yue-Shuai (Frontiers in Physiology, 2025)
ObjectiveThis study aims to compare the efficacy of mHealth-based exercise interventions with traditional exercise in improving pain intensity, functional disability, and quality of life in patients suffering from knee osteoarthritis (OA).MethodRandomized controlled trials (RCTs) published from their inception to 23 August 2024 were searched in Cochrane, Embase, Medline, Web of Science. Reviewer pairs independently extracted data and evaluated bias using the Cochrane Risk of Bias tool.ResultsEleven studies, with a total of 800 participants with a mean age of 55.51 ± 6.88 years, were identified. All RCTs were performed from 2013 to 2024. There was no statistically significant difference between mHealth-supported exercise compared with the traditional exercise without mHealth in terms of pain reduction (standard mean differences [SMD] = −0.35; 95%CI: −0.74 to 0.04, P = 0.08), functional disability (SMD = −0.5; 95%CI: −0.1 to 0.01; P = 0.05), and quality of life (SMD = 0.11; 95%CI: −0.26 to 0.48; P = 0.56). However, a statistically significant difference was found between mHealth-supported exercise compared with unsupervised traditional exercise in terms of pain (SMD = −1.03; 95%CI: −1.49 to −0.57; P < 0.001) and functional disability (SMD = −0.89; 95%CI: −1.71 to −0.06; P = 0.04).ConclusionmHealth-based exercise was found to be more effective than unsupervised conventional exercise in promoting pain relief and enhancing functional disability in patients with OA. When face-to-face exercise intervention is not feasible, mHealth-based exercise should be considered a viable option in the recovery process for knee OA. Given the significant heterogeneity observed in this study, it is important to exercise caution when extrapolating the results.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier CRD42024610393.